2019
DOI: 10.1038/s41598-019-55053-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrative proteomics and phosphoproteomics in pulmonary arterial hypertension

Abstract: Pulmonary arterial endothelial cells (PAEC) are mechanistically linked to origins of pulmonary arterial hypertension (PAH). Here, global proteomics and phosphoproteomics of PAEC from PAH (n = 4) and healthy lungs (n = 5) were performed using LC-MS/MS to confirm known pathways and identify new areas of investigation in PAH. Among PAH and control cells, 170 proteins and 240 phosphopeptides were differentially expressed; of these, 45 proteins and 18 phosphopeptides were located in the mitochondria. Pathologic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 65 publications
12
78
0
Order By: Relevance
“…In the GO-based assessment using Database for Annotation, Visualization and Integrated Discovery, we focused on pathways closely associated with the mitochondria and were implicated in proliferation. Proteomic evidence from a recent report by Xu Weiling et al 29 showed that endothelial cells derived from human PAH patients had deranged mitochondrial respiration, abnormal FA metabolism, enhanced oxidative stress, and apoptosis resistance. 29 The study concluded that PAH is characterized by metabolic pathways that are primarily associated with the mitochondria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the GO-based assessment using Database for Annotation, Visualization and Integrated Discovery, we focused on pathways closely associated with the mitochondria and were implicated in proliferation. Proteomic evidence from a recent report by Xu Weiling et al 29 showed that endothelial cells derived from human PAH patients had deranged mitochondrial respiration, abnormal FA metabolism, enhanced oxidative stress, and apoptosis resistance. 29 The study concluded that PAH is characterized by metabolic pathways that are primarily associated with the mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic evidence from a recent report by Xu Weiling et al 29 showed that endothelial cells derived from human PAH patients had deranged mitochondrial respiration, abnormal FA metabolism, enhanced oxidative stress, and apoptosis resistance. 29 The study concluded that PAH is characterized by metabolic pathways that are primarily associated with the mitochondria. 29 In addition to this, other reports also indicated that dysregulation of oxidative phosphorylation, FA metabolism, oxidative stress, and regulation of apoptosis were significantly associated with PAH and proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the down-regulated proteins were related to mitochondrial structure and function(Malenfant et al, 2015). A recent proteomic study in pulmonary arterial endothelial cells obtained from PAH patients after lung transplantation found that changes of protein levels in these pulmonary cells can be linked to the mitochondria(Xu et al, 2019). An analysis of 1,124 plasma proteins from a defined PAH population using the 1K Somamer platform established the potential clinical utility of proteome screening of venous blood; a nine-protein panel was defined that predicts survival at baseline in PAH with an accuracy equivalent to clinical measures, such as provided by the REVEAL prognostic equation(Benza et al, 2019;.The proteins cover a range of pathological processes relevant to PAH, such as myocardial stress (IL-1 receptor-like 1 also known as ST-2), pulmonary endothelial repair (tissue inhibitors of metalloproteinases, TIMPs −1 and −2), inflammation and metabolism (insulin growth factor binding protein-1 and apolipoprotein E), innate immunity (complement factors H, reduced and D, increased), abnormal iron status (erythropoietin) and thrombogenesis (reduced plasminogen).…”
mentioning
confidence: 99%